(untitled) (Applied Biological Research, 2015)
A study was undertaken to assess the function of aldosterone as oxidative stress marker in lambs of Marwari breed during extreme hot ambience.Radio immunometric assay was used to determine serum aldosterone. Results revealed significant (p0.05) increase in serum aldosterone, γ glutamyl transferase (GGT), sodium and chloride contents during hot ambience as compared to moderate ambience. Serum potassium, calcium, phosphorus and magnesium showed reverse trend and the values were significantly lower during hot ambience as compared to moderate ambience. Maximum per cent change was observed in serum GGT, thus establishing the oxidative stress. A relationship of aldosterone with oxidative stress was observed. Results visibly validated that besides diseases, ambient stress can put in variations in aldosterone with the establishment of oxidative stress.